2019
DOI: 10.1002/aps.1634
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between antisocial and obsessive‐compulsive personality characteristics in cult‐like religious groups: A psychodynamic decoding of the DSM‐5

Abstract: The antisocial and violent behaviors of cult‐like religious groups (CRGs) and the maladaptive social consequences of their activities suggest clinical or character pathology and invite diagnostic and dynamic formulations of their members' personalities. The current study utilized secondary reports in the commercial media about CRG members, combined with the lived experience method of two of the authors. The resulting core characteristics of CRG members were then classified following the alternative DSM‐5 alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Emotions, in particular, play an important role in extreme overvalued belief, and often paradoxically include both positive and negative affect states. For example, lone actor terrorists and some group‐based terrorists will often feel moral outrage toward a perceived victimized group, and vicariously identify with that group, feeling anger and humiliation, and other dysphoric states (Meloy & Gill, 2016; Rahmani, Hemmati, Cohen, & Meloy, 2019). As they move on a pathway toward violence, the identification with the victimized group becomes an identification as a warrior or soldier to defend the victimized group, accompanied by feelings of exhilaration and excitement, and other euphoric states (Meloy, 2017).…”
Section: Extreme Overvalued Beliefmentioning
confidence: 99%
“…Emotions, in particular, play an important role in extreme overvalued belief, and often paradoxically include both positive and negative affect states. For example, lone actor terrorists and some group‐based terrorists will often feel moral outrage toward a perceived victimized group, and vicariously identify with that group, feeling anger and humiliation, and other dysphoric states (Meloy & Gill, 2016; Rahmani, Hemmati, Cohen, & Meloy, 2019). As they move on a pathway toward violence, the identification with the victimized group becomes an identification as a warrior or soldier to defend the victimized group, accompanied by feelings of exhilaration and excitement, and other euphoric states (Meloy, 2017).…”
Section: Extreme Overvalued Beliefmentioning
confidence: 99%
“…This is at odds with findings from other studies which found a negative association between religiosity (as indexed by fasting during Ramadan) and the likelihood of terror events [53]. However, a study that examined the intricate relationship between religiosity, personality disorder, and violence through the prism of social relations theory, highlighted the significance of antisocial and obsessive‐compulsive characteristics, which are reportedly common among religious extremists [54].…”
Section: Discussionmentioning
confidence: 81%
“…Emotions in particular play an important role in last resort thinking and behavior and paradoxically appear to include both positive and negative affect states. Meloy and Rahman (2021) wrote about this in relation to the pathway to violence and extreme overvalued beliefs:Lone actor terrorists and some group-based terrorists will often feel moral outrage toward a perceived victimized group, and vicariously identify with that group, feeling anger and humiliation, and other dysphoric states (Meloy & Gill, 2016; Rahmani et al, 2019). As they move on a pathway toward violence, the identification with the victimized group becomes an identification as a warrior or soldier to defend the victimized group, accompanied by feelings of exhilaration and excitement, and other euphoric states (Meloy, 2017).…”
Section: Phenomenologymentioning
confidence: 99%
“…Lone actor terrorists and some group-based terrorists will often feel moral outrage toward a perceived victimized group, and vicariously identify with that group, feeling anger and humiliation, and other dysphoric states (Meloy & Gill, 2016; Rahmani et al, 2019). As they move on a pathway toward violence, the identification with the victimized group becomes an identification as a warrior or soldier to defend the victimized group, accompanied by feelings of exhilaration and excitement, and other euphoric states (Meloy, 2017).…”
Section: Phenomenologymentioning
confidence: 99%